Propofol Exposure Disturbs the Differentiation of Rodent Neural Stem Cells via an miR-124-3p/Sp1/Cdkn1b Axis - Cao, Jun; Li, Yan; Zeng, Fanning; Liu, Xiaolei; Tao, Tao; Qin, Zaisheng (Frontiers in Cell and Developmental Biology, 2020)
Accumulating studies have indicated that propofol may lead to neurotoxicity and its effect on neural stem cells (NSCs) may play pivotal role in propofol-related neurotoxicity. Previously, we found that propofol could promote NSCs proliferation and could regulate several microRNA expressions. However, the underlying mechanism between microRNAs and NSCs development after propofol exposure is still unclear. Our data first observed that rat primary neural stem cells exposed to propofol exhibited a cell cycle arrest status and an inclination to differentiate into GFAP+ or S100β+ cells. This phenomenon was accompanying with a lower miR-124-3p expression and could be reversed via overexpression miR-124-3p in NSCs. Using bioinformatic predictions and luciferase assay we confirmed that Sp1 (Specificity Protein 1) is the target gene of miR-124-3p, indicating that miR-124-3p may regulate NSCs development through Sp1. Further, knockdown of Sp1 rescue the effect of propofol on NSCs differentiation. Finally, we demonstrated that Sp1 could bind cdkn1b promoter region through chromatin immunoprecipitation assay, indicating that Sp1 affect NSC’s cell cycle through cdkn1b directly. Overall, our study highlights the miR-124-3p/Sp1/cdkn1b axis to be important in propofol interfering the differentiation of NSCs.